Penafsiran Esensial tentang Kasih 1 Yohanes 4 : 7-12 : Kasih yang Memampukan Kita Menjadi Serupa dengan Kristus - Adelia Tamo Ina; Malik Bambangan (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Love is a central theme in the Christian faith, as stated in 1 John 4:7-12. This letter confirms that love comes from God, and love is the essence of God's existence and character. This article examines in depth the concept of divine love (agape) in 1 John, which is demonstrated through the sending of Jesus Christ as an atoning sacrifice for human sins. Using a hermeneutic approach and textual analysis, this article explores how God's love enables believers to reflect the character of Christ in everyday life. Through true love, believers are called to live in harmony with others as proof of their knowledge of God. Love in this context is not only a moral act, but a spiritual transformation that signifies spiritual maturity and a life in line with God's will.